Clinical treatment of avulsed tooth, data from literature - Robo, Ilma; Kelmendi, Manola; Habazaj , Eva; Miri , Alda; Heta , Saimir; Alliu , Nevila (International Journal of Dental Research, 2025)
Background: The most dangerous outcome of a tooth avulsion, independent of the tooth's “kind” or “position” inside the oral cavity, is destruction of periodontal ligament and pulpal necrosis. Very few live cells with the capacity to heal the damaged ligament, are left on the surface of the tooth. In actuality, the patient is not accountable for and is not even able to handle the injuries caused by the tooth colliding with the alveolus, or the cement colliding with the alveolar walls. Even if these blemishes are minor, the cement is harmed. Methods: The primary focus of this research is to collect data that has previously been released on the therapy protocol for avulsed teeth and the features of the variables which influence the effective completion of re-implantation in line with the previously established procedures. There are 20 publications that require to be examined in more detail. They will be classified initially based on the approach that was em-ployed for assessing the results and then by their year of publication of the article. Results: Apexification is believed to be important in 12% of cases if it pertains to a re-implanted tooth's prognosis. A component that was not truly included in the timetable for putting out the re-implantation procedure. The results show that fifteen percent of the prognostic of re-implanted teeth can be attributed to vitality of alveolar bone. The eventual fate of a tooth which has been reimplanted remains unaltered by bone vitality. The one element related to this process is alveolar bone, that is always essential. There's an absolute lack of information con-cerning the pulp vitality factor considering that we are talking about re-implanted teeth, not luxated teeth, and every single re-implanted tooth has an indication for endodontic treatment. Conclusions: The loss of periodontal ligament's normal physiological metabolism and the morphology of the cells which make up the liga-ment, decrease if periodontal ligament dried up. All of these factors depend on the speed at which the re-implantation procedure continues, preferably in the first fifteen to twenty minutes after avulsion. The nurse or emergency doctor performing this procedure must be familiar with re-implantation or receive medical care for this. If not, a dentist has to give this information over the phone as soon as possible. The tooth “needs” to be washed and carefully placed in the empty alveolus, paying care to keep the shape of both elements, the tooth and the alveolus.